2010
DOI: 10.1590/s1678-77572010000500004
|View full text |Cite
|
Sign up to set email alerts
|

Sexual harassment in Dentistry: prevalence in dental school

Abstract: ObjectiveSexual harassment is unlawful in all work and educational environments in most nations of the world. The goals of this study were to describe the sexual harassment prevalence and to evaluate the experiences and attitudes of undergraduate students in one dental school in Brazil.Material and MethodsAn 18-item questionnaire was administered to 254 dental students with a completion rate of 82% (208). Students were requested to respond to questions about their background and academic level in dental school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 17 publications
(40 reference statements)
0
32
0
3
Order By: Relevance
“…Despite the enactment of a Brazilian law in 2001 raising the punishment for sexual harassment to one to two years of jail time, there is still no official legislative act to address sexual discrimination in educational environments 37 . One study conducted at a dental school in Brazil found that 15% of its students had experienced sexual harassment by a patient, relative, or faculty member 10 . That study found that male students were three times more likely to be sexually harassed than female students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the enactment of a Brazilian law in 2001 raising the punishment for sexual harassment to one to two years of jail time, there is still no official legislative act to address sexual discrimination in educational environments 37 . One study conducted at a dental school in Brazil found that 15% of its students had experienced sexual harassment by a patient, relative, or faculty member 10 . That study found that male students were three times more likely to be sexually harassed than female students.…”
Section: Discussionmentioning
confidence: 99%
“…Studies published from 1992 to 2017 found that sexual harassment was pervasive in dental education, 6 10 and one study published in 1994 found evidence of patients’ sexual harassment of their oral health care providers 11 . Reports from dental and dental hygiene students published in the 1990s confirmed that such advances occurred and that students were rarely trained to deal with them effectively 12 – 14 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cinsel taciz "insan onurunu ihlal etme amacına yönelen veya bu sonucu doğuran, istenilmeyen, her türlü cinsel nitelikte sözlü, sözlü olmayan veya özel olarak düşmanca, aşağılayıcı, utandırı-cı ve saldırgan bir ortam yaratan davranış" olarak tanımlanmak-tadır (1,2). Mağdurların psikolojik ve fiziksel sağlığını bozan, eğitim ve iş hayatlarını aksatan, ekonomik yaşamlarını büyük oranda etkileyen bir durumdur (1,3).…”
Section: Gi̇ri̇ş Ve Amaçunclassified
“…Cinsel taciz tüm dünyada yasalarca cezalandırılmıştır (2,5). Türk Ceza Kanunu'nun 105. maddesinde de, cinsel taciz suçunun, mağdurun şikâyeti üzeri-ne, üç aydan iki yıla kadar hapis cezası ile cezalandırılacağı, suçun hiyerarşi veya hizmet ilişki-sinden kaynaklanan nüfuz kötüye kullanılmak suretiyle ya da aynı işyerinde çalışmanın sağladığı kolaylıktan yararlanılarak işlen-mesi halinde cezanın yarı oranında artırılacağı belirlenmiştir (6).…”
Section: Gi̇ri̇ş Ve Amaçunclassified